Development of the Evaluation System of Islamic Education in Indonesian Pondok Pesantren - Nailil Maghfiroh; Saadi; Mukh Nursikkin (At Turots: Jurnal Pendidikan Islam, 2023)
This research aims to explore the concept of evaluation in the Quran, innovations in developing evaluation for Islamic education (PAI) in traditional and "Wahhabi" Salafi pesantren, as well as an analysis of the innovation in developing PAI evaluation in both types of pesantren. The method used in this research is field research and library research, which involves gathering data related to the research theme from books and journal articles related to the discussion. The results of this research indicate that education evaluation in the Quran plays an important role and is mentioned in several verses. Traditional Salafi pesantren and "Wahhabi" Salafi pesantren are educational institutions that develop an evaluation system in PAI learning, which includes daily, weekly, monthly, semesterly, end-of-year, and end-of-level evaluations, using various evaluation methods. The development of the PAI evaluation system in traditional and "Wahhabi" Salafi pesantren is in line with the perennialist philosophy theory. The evaluation development is valid, competence-oriented, continuous, comprehensive, meaningful, fair and objective, open, recorded and accurate, and systematic. They both have many similarities in their evaluation systems, but differ in their evaluation outcome orientation.